A coupled volume-of-fluid/level-set method for simulation of two-phase flows on unstructured meshes. (2nd January 2016) - Balcázar, Néstor; Lehmkuhl, Oriol; Jofre, Lluís; Rigola, Joaquim; Oliva, Assensi
Highlights: A VOF/LS method is introduced for simulation of two-phase flows on unstructured meshes. A VOF-PLIC method is used for interface advection. Surface tension force is calculated using a the level-set function. Numerical results are in excellent agreement with experiments from literature. Abstract: This paper presents a methodology for simulation of two-phase flows with surface tension in the framework of unstructured meshes, which combines volume-of-fluid with level-set methods. While the volume-of-fluid transport relies on a robust and accurate polyhedral library for interface advection, surface tension force is calculated by using a level-set function reconstructed by means of a geometrical procedure. Moreover the solution of the fluid flow equations is performed through the fractional step method, using a finite-volume discretization on a collocated grid arrangement. The numerical method is validated against two- and three-dimensional test cases well established in the literature. Conservation properties of this method are shown to be excellent, while geometrical accuracy remains satisfactory even for the most complex flows.